Kinetic-Spectrophotometric Determination of Trace Amounts of Formaldehyde Based on Its Catalytic Effect on Oxidation of Neutral Red in Acidic Media - Pourreza, N.; Parham, H.; Cheraghi, S. (Asian Journal of Chemistry, 2016)
A simple, sensitive and rapid kinetic-spectrophotometric method for the determination of trace amounts of formaldehyde is reported. The method is based on the catalytic effect of formaldehyde on the rate of oxidation of neutral red by bromate in acidic media at 33°C. The reaction is monitored spectrophotometrically by measuring the decrease in absorbance of neutral red at 524 nm using a variable time method. The method shows two linear calibration graphs in the concentration ranges of 25–600 ng mL–1 and 0.6–6.0 μg mL–1 of formaldehyde. The limit of detection is 23 ng mL–1 and the relative standard deviation for ten replicate measurements of 1 μg mL–1 of formaldehyde is 0.93%. The method was successfully applied to the determination of formaldehyde in melamine-formaldehyde resins.